The Influence of Investment Opportunity Set, Firm Size, Profitability, Leverage, and Liquidity on Dividend Policy in Food and Beverage Companies Listed on the Indonesia Stock Exchange - Wahyu Diatmika, I Ketut Mudana; Widhiastuti, Ni Luh Putu; Novitasari, Ni Luh Gde (AIBPM Publisher, 2025)
Dividend policy is a company decision regarding whether the profits earned in a given period will be distributed to shareholders in the form of dividends or retained as retained earnings to finance future investment needs. The purpose of this study is to determine the effect of investment opportunity set, firm size, profitability, leverage, and liquidity on dividend policy in food and beverage sector companies listed on the Indonesia Stock Exchange (IDX) for the 2022-2024 period. The population of this study consists of food and beverage sector companies listed on the Indonesia Stock Exchange during the 2022-2024 period. The sample was determined using a purposive sampling technique, resulting in a total of 28 companies with a research period of three years. The data analysis technique used in this study is multiple linear regression analysis. The results of the study show that the investment opportunity set has a negative effect on dividend policy, and profitability has a positive effect on dividend policy. Meanwhile, firm size, leverage, and liquidity have no effect on dividend policy in food and beverage sector companies listed on the IDX for the 2022-2024 period